The results of cardiopulmonary exercise test in healthy Korean children and adolescents: single center study - Jun-Sook Lee; So-Ick Jang; Seong-Ho Kim; Sang-Yun Lee; Jae-Suk Baek; Woo-Sup Shim (Korean Pediatric Society, 2013)
PurposeThe cardiopulmonary exercise test (CPET) is an important clinical tool for evaluating exercise capacity and is frequently used to evaluate chronic conditions including congenital heart disease. However, data on the normal CPET values for Korean children and adolescents are lacking. The aim of this study was to provide reference data for CPET variables in children and adolescents.MethodsFrom August 2006 to April 2009, 76 healthy children and adolescents underwent the CPET performed using the modified Bruce protocol. Here, we performed a medical record review to obtain data regarding patient' demographics, medical history, and clinical status.ResultsThe peak oxygen uptake (VO2Peak) and metabolic equivalent (METMax) were higher in boys than girls. The respiratory minute volume (VE)/CO2 production (VCO2) slope did not significantly differ between boys and girls. The cardiopulmonary exercise test data did not significantly differ between the boys and girls in younger age group (age, 10 to 14 years). However, in older age group (age, 15 to 19 years), the boys had higher VO2Peak and METMax values and lower VE/VCO2 values than the girls.ConclusionThis study provides reference data for CPET variables in case of children and adolescents and will make it easier to use the CPET for clinical decision-making.